A Building‐Integrated Hybrid Photovoltaic‐Thermal (PV‐T) Window for Synergistic Light Management, Electricity and Heat Generation - Francesco Polito; Gan Huang; Christos N. Markides (Advanced Science)
Abstract The installation of common solar panels and collectors in the built environment requires access to significant roof space, which is limited. This motivates the development of high‐efficiency, building‐integrated technologies that can maximize space utilization and energy provision. In this work, a building‐integrated hybrid photovoltaic‐thermal window (PVTW) is fabricated and tested, composed of a semi‐transparent photovoltaic (PV) layer and a selectively absorptive liquid‐based thermal absorber. It is demonstrated that, at 30° inclination, the PVTW can simultaneously generate electricity, with an electrical efficiency of 3.6%, and provide ≈50 °C water, with a thermal efficiency of 10.7%, in the middle of a typical summer day (20th July) in London (maximum ambient temperature ≈34 °C, solar irradiance ≈1100 W m−2 at midday). The water temperature decreases by ≈7 °C, whilst thermal efficiency improves to 17.6% as the inclination angle increases to 90° (vertical); the electrical efficiency reduces marginally (3.3%). Compared to a liquid‐based solar‐thermal window (STW), the PVTW can generate hot water at ≈10 °C higher temperature and with 10% absolute increase in thermal efficiency when the inclination angle is 60°, plus electricity. The wider uptake of this technology in glass‐based urban spaces has the potential to generate significant energy while reducing building temperature management costs.